Interferon α-inducible protein 27 is an oncogene and highly expressed in cholangiocarcinoma patients with poor survival - Chiang K; Huang S; Wu RC; Huang SC; Yeh T; Chen M; Hsu JT; Chen L; Kuo SF; Chueh H; Juang H; Hung S; et al. (Cancer Management and Research, 2019)
Kun-Chun Chiang,1 Sheng-Teng Huang,2 Ren-Chin Wu,3 Shih-Chiang Huang,3 Ta-Sen Yeh,4 Ming-Huang Chen,5 Jun-Te Hsu,4 Li-Wei Chen,6 Sheng-Fong Kuo,7 Ho-Yen Chueh,8 Horng-Heng Juang,9 Shuen-Iu Hung,10 Chun-Nan Yeh,4 Jong-Hwei S Pang11,12 1General Surgery Department, Chang Gung Memorial Hospital, Chang Gung University, Keelung, Taiwan, ROC; 2Department of Chinese Medicine, China Medical University Hospital, Taichung, Taiwan, ROC; 3Department of Anatomic Pathology, Chang Gung Memorial Hospital, Kwei-Shan, Chang Gung University, Taoyuan, Taiwan, ROC; 4General Surgery Department, Chang Gung Memorial Hospital, Kwei-Shan, Chang Gung University, Taoyuan, Taiwan, ROC; 5Division of Hematology and Oncology, Department of Medicine, Taipei Veterans General Hospital, Faculty of Medicine, National Yang-Ming University, Taipei, Taiwan, ROC; 6Department of Gastroenterology, Chang Gung Memorial Hospital, Chang Gung University, Keelung, Taiwan, ROC; 7Department of Endocrinology and Metabolism, Chang Gung Memorial Hospital, Chang Gung University, Keelung, Taiwan, ROC; 8Department of Obstetrics and Gynecology, Chang Gung Memorial Hospital, Taoyuan, Taiwan, ROC; 9Department of Anatomy, College of Medicine, Chang Gung University, Kwei-Shan, Taoyuan 333, Taiwan, ROC; 10Department and Institute of Pharmacology, School of Medicine, National Yang-Ming University, Taipei, Taiwan, ROC; 11Graduate Institute of Clinical Medical Sciences, College of Medicine, Chang Gung University, Kwei-Shan, Taoyuan, Taiwan, ROC; 12Department of Physical Medicine and Rehabilitation, Chang Gung Memorial Hospital, Linkow, Taoyuan City, Taiwan, ROC Objective: Cholangiocarcinoma (CCA) is a devastating disease. Interferon α-inducible protein 27 (IFI27), originally known to involve in innate immunity, is later found to intervene in cell proliferation, leading to inventive studies regarding the role of IFI27 in cancer treatment. We aimed to investigate the role of IFI27 in CCA.Materials and methods: Cell proliferation, migration, and invasion assays, Western blot, gene transfection and knockdown, immunofluorescent and immunohistochemical stains, and xenograft animal model were applied.Results: IFI27 knockdown in CCA cells induced cell cycle arrest in S phase, resulting in lower cell proliferative rate in vitro and in vivo. IFI27 knockdown attenuated CCA cell migration and invasion through inhibition of epithelial–mesenchymal transition, which was supported by increased E-cadherin and decreased N-cadherin and fibronectin. Filamentous actin level was also reduced. IFI27 knockdown further repressed expression and secretion of vascular endothelial growth factor (VEGF-A), a strong stimulator of angiogenesis, through downregulation of c-jun and c-fos, which was supported in vitro by the finding that human vascular endothelial cells grew more slowly in conditioned medium of IFI27 knockdown on CCA cells and in vivo by the lower erythropoietin concentration found in the xenografted tumors derived from IFI27 knockdown on CCA cells. In addition, anti-VEGF-A antibody treatment was able to repress CCA cell growth. To the contrary, IFI27 overexpression could increase CCA cell proliferation, migration, and invasion. Clinically, higher IFI27 expression was linked to inferior overall survival of CCA patients.Conclusion: Our data strongly suggest that IFI27 could be deemed as a potential target for CCA treatment. Keywords: IFI27, cholangiocarcinoma, oncogene, angiogenesis, VEGF-A, metastasis, tumor growth, cell cycle